INTERNET OF THINGS-BASED AIR QUALITY ANALYSIS FOR MONITORING CO2 CONCENTRATION IN ROOFTOP BUILDING AREAS - Mandasari, R Deasy; Rosano, Andi; Sudaradjat, Djadjat (BAROMETER, 2024)
This research aims to comprehend the air quality in rooftop areas in the city of DKI Jakarta, renowned for its high population density and rapid infrastructure development. The main focus is on the concentration of carbon dioxide (CO2) in the roof area, serving as an indicator of air quality influenced by air pollution, industrial activity, and heavy transportation. The utilization of Internet of Things (IoT) technology and CO2 sensors proves to be an effective solution for real-time monitoring of CO2 concentrations. This research holds significance for air pollution control measures, providing insight into the impact of rooftop gardens in reducing CO2 emissions and inspiring future research in the realms of air quality and IoT technology. Through prior literature, three notable studies underscore the industrial and technological impact of CO2 monitoring. The research was conducted in two locations in DKI Jakarta, namely the Garden Roof and Ordinary Roof areas. Monitoring took place over four parts of the day with a four-hour interval to compare CO2 levels. The tools employed included the NodeMCU ESP8266, DHT-22 sensor, and MQ-135 sensor. Results revealed that roof areas with gardens exhibited lower average CO2 levels (295 PPM) compared to regular roofs (360 PPM), indicating the potential of garden roof designs to reduce CO2 concentrations. Research recommendations include increasing the frequency of data collection and considering additional factors for a more comprehensive understanding of urban air quality.